MALDI-induced Fragmentation of Leucine enkephalin, Nitro-Tyr Leucine Enkaphalin, and d(5)-Phe-Nitro-Tyr Leucine Enkephalin - Zhan, Xianquan (2009)
The long-term objective of this study is to use MALDI MS and MS/MS to study the fragmentation pattern of in vitro nitrotyrosine-containing peptides in order to assist the interpretation of MS-identification of endogenous nitroproteins in human tissues and fluids. The short-term objective is to study synthetic leucine enkephalin, nitro-Tyr-leucine enkephalin, and d(5)-Phe-nitro-Tyr-leucine enkephalin with a vacuum matrix-assisted laser desorption/ionization linear ion-trap mass spectrometer (vMALDI-LTQ). The results demonstrated the UV laser-induced photochemical decomposition of the nitro group. Although photochemical decomposition decreased the ion intensity and complicated the MS spectrum, the recognition of that unique decomposition pattern unambiguously identified a nitrotyrosine. The a(4)- and b(4)-ions were the most-intense fragment ions found in the MS/MS spectra for those three synthetic peptides. Compared to the unmodified peptides, more collision energy optimized the fragmentation of the nitropeptide, increased the intensity of the a(4)-ion, and decreased the intensity of the b(4)-ion. Optimized laser fluence maximized the fragmentation of the nitropeptide. MS(3) analysis confirmed the MS(2)-derived amino acid sequence, but required much more sample. To detect a nitropeptide, the sensitivity of vMALDI-LTQ is 1 fmol for MS detection and 10 fmol for MS(2) detection; the S/N ratio was ca. 50:1 in those studies. Those data are important for an analysis of low-abundance endogenous nitroproteins, where preferential enrichment of nitroproteins and optimized mass spectrometry parameters are used.